Usage of laparoscopic bilateral nephrectomy in combination with mini-laparotomy in the treatment of patients with autosomal dominant polycystic kidney disease and end-stage chronic renal failure - A. E. Lubennikov; R. N. Trushkin; N. V. Morozov; O. N. Kotenko (Вестник урологии)
Introduction. Laparoscopic bilateral nephrectomy for autosomal dominant polycystic kidney disease has many advantages over open surgery, but a significant disadvantage is the long duration of the intervention, and the need to create access for extraction of large kidneys minimizes the cosmetic effect.Purpose of the study. To improve the outcomes of bilateral nephrectomy in patients with autosomal-dominant polycystic kidney disease.Materials and methods. Study design: a single-centre, retro- and prospective study from 2010 to March 2020, including 72 patients who underwent bilateral nephrectomy. The patients were divided into three groups depending on the nature of the operation: Group I (n = 42), midline laparotomy; Group II (n = 16), laparoscopic surgery and group III (n = 15), combined nephrectomy (the laparoscopic stage included the separation of the vessels of the kidney and ureter, separation of the kidney from the adrenal gland; then, the kidneys were mobilized and removed from the upper midline mini-laparotomy.Results. In group I, the median duration of surgery was 120 min (Q1 - Q3: 110 - 150), in group II — 205 min (Q1 - Q3: 192 - 267) and in the third — 165 min (Q1 - Q3: 145 - 175). The operation time in the third group was significantly higher than in the first (p = 0.049) and significantly lower than in the second group (p = 0.034). There was no significant difference between the groups (p = 0.125) comparing the volume of intraoperative blood loss. There was no significant difference in the incidence of intraoperative complications between the groups. The median access length for laparotomy was 25 cm (Q1 - Q3: 22 - 28), for laparoscopy 14 cm (Q1 - Q3: 14 - 15) and combined surgery — 16 cm (Q1 - Q3: 15 - 17), the differences were reliable. The median bed-day for the second group was 8 days (Q1 - Q3: 7 - 9), for the third — 9 days (Q1 - Q3: 8 - 11).Conclusion. Combined bilateral nephrectomy has all the advantages of laparoscopic surgery, but at the same time, it can significantly reduce the operation time without significantly increasing the length of the surgical approach.